Hyper-acute effects of sub-concussive soccer headers on brain function and hemodynamics - Grijalva, Carissa; Hale, Dallin; Wu, Lyndia; Toosizadeh, Nima; Laksari, Kaveh (Frontiers in Human Neuroscience, 2023)
Sub-concussive head impacts in soccer are drawing increasing research attention regarding their acute and long-term effects as players may experience thousands of headers in a single season. During these impacts, the head experiences rapid acceleration similar to what occurs during a concussion, but without the clinical implications. The physical mechanism and response to repetitive impacts are not completely understood. The objective of this work was to examine the immediate functional outcomes of subconcussive level impacts from soccer heading in a natural, non-laboratory environment. Twenty university level soccer athletes were instrumented with sensor-mounted bite bars to record impacts from 10 consecutive soccer headers. Pre-and post-header measurements were collected to determine hyperacute changes, i.e., within minutes after exposure. This included measuring blood flow velocity using transcranial Doppler (TCD) ultrasound, oxyhemoglobin concentration using functional near infrared spectroscopy imaging (fNIRS), and upper extremity dual-task (UEF) neurocognitive testing. On average, the athletes experienced 30.7±8.9 g peak linear acceleration and 7.2±3.1 rad/s peak angular velocity, respectively. Results from fNIRS measurements showed an increase in the brain oxygenation for the left prefrontal cortex (PC) (p=0.002), and the left motor cortex (MC) (p=0.007) following the soccer headers. Additional analysis of the fNIRS time series demonstrates increased sample entropy of the signal after the headers in the right PC (p=0.02), right MC (p=0.004), and left MC (p=0.04)., as well as increased tissue saturation index in the left PC (p=0.0002), right PC (p=0.01), left MC (p<0.0001), and right MC (p=0.01). These combined results reveal some variations in brain activation oxygenation immediately detected after repetitive headers. Significant changes in balance and neurocognitive function were not observed in this study, indicating a mild level of head impacts. This is the first study to observe hemodynamic changes immediately after sub-concussive impacts using non-invasive portable imaging technology. In combination with head kinematic measurements, this information can give new insights and a framework for immediate monitoring of sub-concussive impacts on the head.